2018
DOI: 10.1021/jacs.7b11303
|View full text |Cite
|
Sign up to set email alerts
|

Parameterization and Analysis of Peptide-Based Catalysts for the Atroposelective Bromination of 3-Arylquinazolin-4(3H)-ones

Abstract: We report the development of a method to parameterize and predict the performance of structurally flexible β-turn-containing peptide catalysts, using the atroposelective bromination of 3-arylquinazolin-4(3H)-ones as a case study. The multivariate correlations obtained for tetrapeptides of two β-turn types, type I′ pre-helical and type II′ β-hairpin, indicate that while one conformer may be associated with a more dominant contribution to the observed enantioselectivity, it is possible that multiple conformers c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
44
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 63 publications
(45 citation statements)
references
References 37 publications
1
44
0
Order By: Relevance
“…12 Recent studies by Miller as well as Thiele and Schreiner showed that even peptidic catalysts with rigidifying turn motifs adopt more than one structure but can be highly stereoselective. [13][14][15][16] Despite these examples, there is still little knowledge about the conformational features that are ideal to achieve highly reactive and stereoselective peptidic catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…12 Recent studies by Miller as well as Thiele and Schreiner showed that even peptidic catalysts with rigidifying turn motifs adopt more than one structure but can be highly stereoselective. [13][14][15][16] Despite these examples, there is still little knowledge about the conformational features that are ideal to achieve highly reactive and stereoselective peptidic catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…22 In fact, it is even possible to correlate selectivity outcomes with different conformations of the same catalyst, suggesting that different transition state ensembles can contribute to the overall selectivity. 23 Yet, the explicit treatment of the conformational dynamics in such flexible catalysts remains a tremendous challenge and currently represents a gap in the field.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, the validity of these SAPT computations was compared to the strength of the H-bond as determined through NBO analysis. [30,31] The single-point energy of the two molecules at the equilibrium distance (identified by SAPT) was computed at the M06-2X/def2-TZVP level of theory, and the energy of the orbital overlap between the S=O oxygen lone pair 1 with the C−H σ* orbital according to NBO recorded (Table S2). A strong correlation between the equilibrium distance by SAPT with the DFT H-bond strength was identified (R 2 = 0.93).…”
Section: Oxygen Atoms As Hydrogen-bond Acceptorsmentioning
confidence: 99%